Subtotal colectomy with antiperistaltic cecorectoanastomosis - V. I. Pomazkin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. To estimate results of subtotal colectomy with antiperistaltic cecorectoanastomosis without dislocation of ascending colon and caecum.Material and methods. Operation is executed at 25 patients. From them 20 patients are operated for chronic constipation with delayed passage through the large intestine (1-st group) and 5 patients with colostomas underwent simultaneous resection of affected regions of the large intestine, liquidation of stoma and restitution of continuity of intestinal tract (2-nd group).Results. No postoperative complications were found. In 1 month at 11 patients periodically had frequent defecations requiring medicamental treatment. In 6 months after surgery average frequency of defecations in the 1-st group was 1,7 per day, in the 2-nd – 2,2 per day.Conclusion. A subtotal colectomy with antiperistaltic cecorectoanastomosis is a simple and effective method of operative treatment of both severe cologenic constipation, and other diseases demanding resection of the most part of the colon.